Efficiency with Costly Information: A Reinterpretation of Evidence from Managed Portfolios - Elton, Edwin J.; Gruber, Martin J.; Das, Sanjiv; Hlavka, Matthew (Review of Financial Studies, 1993)
[We investigate the informational efficiency of mutual fund performance for the period 1965-84. Results are shown to be sensitive to the measurement of performance chosen. We find that returns on S&P stocks, returns on non-S&P stocks, and returns on bonds are significant factors in performance assessment. Once we correct for the impact of non-S&P assets on mutual fund returns, we find that mutual funds do not earn returns that justify their information acquisition costs. This is consistent with results for prior periods.]